An FCM–FAHP approach for managing readiness-relevant activities for ERP implementation. (October 2015) - Ahmadi, Sadra; Yeh, Chung-Hsing; Papageorgiou, Elpiniki I.; Martin, Rodney
Highlights: An approach for managing readiness-relevant activities using FCM and FAHP is proposed. The approach models causal relationships between readiness-relevant activities. It also assesses how these activities contribute to the overall readiness. A management matrix for effective allocation of limited management efforts is provided. Scenario analysis was accomplished to work out a readiness improvement plan. Abstract: Any organization which plans to introduce a new enterprise resource planning (ERP) system will carry out a range of activities to improve its readiness for the new system. This paper develops a new approach for managing these interrelated activities using fuzzy cognitive maps (FCMs) and the fuzzy analytical hierarchy process (FAHP). This approach enables the organization to (1) identify the readiness-relevant activities, (2) determine how these activities influence each other, (3) assess how these activities will contribute to the overall readiness and (4) prioritize these activities according to their causal interrelationships to allocate management effort for the overall readiness improvement. The approach first uses FCMs and a fuzzy connection matrix to represent all possible causal relationships between activities. It then uses FAHP to determine the contribution weights and uses FCM inference to include the effects of feedback between the activities. Based on the contribution and interrelationships between activities, a management matrix is developed to categorize them into four management zones for effective allocation of limited management efforts. An empirical study is conducted to demonstrate how the approach works.